Aerodynamics and Modal Analysis for the Combined Vane type Vertical Axis Wind Turbine - H. Suffer, Kadhim; Y. Kahtan, Yassr; M. Razlan, Zuradzman (International Journal of Engineering and Technology, 2018)
The present global energy economy suggests the use of renewable sources such as solar, wind, and biomass to produce the required power. The vertical axis wind turbine is one of wind power applications. Usually, when the vertical axis wind turbine blades are designed from the airfoil, the starting torque problem begins. The main objective of this research is to numerically simulate the combination of movable vanes of a flat plate with the airfoil in a single blade configuration to solve the starting torque problem. CFD analysis in ANSYS-FLUENT and structural analysis in ANSYS of combined blade vertical axis wind turbine rotor has been undertaken. The first simulation is carried out to investigations the aerodynamic characteristic of the turbine by using the finite volume method. While the second simulation is carried out with finite element method for the modal analysis to find the natural frequencies and the mode shape in order to avoid extreme vibration and turbine failure, the natural frequencies, and their corresponding mode shapes are studied and the results were presented with damping and without damping for four selected cases. The predicted results show that the static pressure drop across the blade increase in the active blade side because of the vanes are fully closed and decrease in the negative side because of the all the vanes are fully open. The combined blade helps to increase turbine rotation and so, thus, the power of the turbine increases. While the modal results show that until the 5th natural frequency the effect of damping can be neglected. The predicted results show agreement with those reported in the literature for VAWT with different blade designs.Â Â Â